THE EFFECT OF TRAINING AND PRACTICE OF AAL CADETS IN KAL CADET IN ORDER TO SUPPORT SHIP CONTROL SKILLS IN KRI - Azi Wardiana; Eska Wiratama; Anton Nugroho (JOURNAL ASRO, 2022)
The task of the Navy in Article 9 of Law number 34 of 2004 concerning the Indonesian National Army, this also includes the achievement of superior human resources of the Navy. To implement the excellence of AAL graduate officers, 60% of AAL's educational operations use training and practical methods, including Ship Control Lattek using KAL Cadets. The aim of this research is to analyze how the influence of AAL cadet training at KAL Cadet on ship control skills in KRI. The research method used is descriptive quantitative. With the problem of the effectiveness of AAL cadet practice training at KAL Cadets in supporting ship control skills in the KRI, this research method is the effectiveness of cadet training is variable (X1) and cadet practice is variable (X2) and the use of equipment (X3) which affects the variable (Y) namely ship control skills. Based on the research, it can be concluded that the variables of ship control training, ship control practices and the use of ship control equipment simultaneously have a significant influence on ship control skills in the KRI. In harmony with effectiveness, which has an understanding of usability, activity and the existence of conformity in an activity between someone who carries out a task with the goal to be achieved. Keywords: AAL, effectiveness, KAL, ship control, cadets